O elemento transponível mariner e o acúmulo de transposição somática no desenvolvimento de Drosophila - Pereira, Camila de Moura (2017)
Transposable elements (TEs) are sequences of DNA with the ability to move inside host genomes. Some TEs are able to transpose into somatic tissues, process called Somatic Transposition (ST) that can be involved with aging, neurodegenerative diseases and cancer. The mariner element is a TE able to move in both somatic cells and germline. A nonautonomous mariner was discovered as a cause of the white-peach mutation in Drosophila eyes. The insertion of this element in the promoter region of the white gene leads to flies with peach colored eyes. In the presence of autonomous copies, the mariner in the white gene can transpose, reversing the mutation and leading to flies with mosaic phenotype (white-peach colored eyes with red spots). This model makes possible to measure the rate of ST by the number of red spots in mosaic flies, because every spot represents an excision event and as a consequence, a ST event. In this study, we used mild heat stress to induce mariner transposition through different stages of D. simulans white-peach test development in order to verify if ST events accumulate in Drosophila. The mariner ST was not constant during the development: the larval stage showed the higher ST rates; pupal stage exhibited less than larval; and transposition was not detected during the embryogenesis. The development stage and the cellular process involved in this period can affect mariner transposition: more intense cell division phases may facilitate it. ST accumulation does not occur linearly, but it may vary by the stages with highest or lowest transposition. The mariner activation under thermal stress was confirmed by qPCR that indicated twice as high rates of ST in the larval stage at 28ºC. Besides, these analyses also showed an accumulation of ST throughout the development.